Strength analysis of the roller bearing with a crowning and misalignment error. (May 2021) - Li, Shuting
Highlights: A new algorithm and mathematical model proposed for strength analyses of roller bearings. New FEM software developed for contact analysis of roller bearings. The maximum shear stresses happened at the contact boundaries of rollers. A best roller-crowning method proposed for the roller-crowning. Abstract: This article aims to present a reliable method that can conduct loading-capacity calculations and strength analyses of roller bearings. A new algorithm and mathematical model are proposed in this paper to realize the purposes through building deformation compatibility relationships and load equilibrium relationships among the outer ring, rollers and the inner ring using mathematical programming method and three-dimensional, finite element method. Special software is developed through many years of efforts to realize the analysis procedures. Contact analysis of a roller bearing is conducted successfully by the developed software. It is found that edge-loads of the roller bearing are analyzed successfully by the developed software when the rollers are not crowned. It is also found that the edge-loads are disappeared and the contact pressure on roller surface becomes a uniform distribution when the rollers are crowned. The effect of quantity of roller-crowning on the contact pressure distribution of rollers is also investigated. It is found that the maximum contact pressure can be reduced about 11% if the quantity of roller-crowning is determined by the maximum roller load. Shear stresses inside the rollers are also analyzed. It is found that the maximum shear stresses exist at the two ends of rollers and near the contact boundaries of the rollers. This means that the roller bearing shall have a fatigue failure at the two ends and near the contact boundaries of the rollers, not at the center of the contact area of the rollers. Finally, contact pressure distribution is analyzed successfully for the roller bearing with a misalignment error.